Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

The standard form is ax + by = c so 3x + y = 2 is already its standard form.

-KookEin

-KookEin

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

It is already in standard form.

But if you wanted to convert it into the form:

y = mx + b

or the SLOPE INTERCEPT FORM,

what we will do is:

3x + y = 2

-3x -3x subtract 3x on both sides

y = 2 - 3x

But if you wanted to convert it into the form:

y = mx + b

or the SLOPE INTERCEPT FORM,

what we will do is:

3x + y = 2

-3x -3x subtract 3x on both sides

y = 2 - 3x

**y = -3x + 2**